Results of the Survey of the Technical Condition of A NineStorey Reinforced Concrete Frame Public Building (Texas Journal of Engineering and Technology, 2023)
This article presents the results of a comprehensive survey of a nine-story reinforced concrete frame public building. In this case, non-destructive testing methods were used to assess the stress-strain state of the bearing elements. To calculate the bearing capacity and resistance to seismic loads of such buildings, the real strength of concrete and the consumption of reinforcement in structures are required. Based on the data obtained, the building was calculated for the first and second limit states in accordance with the current regulatory documents and, based on their results, practical recommendations were issued to ensure the seismic resistance of this building